A165 ASSESSING ATTENDANCE OF SUBSTANCE USER ENDOSCOPIES (A.S.U.R.E). (26th February 2020) - Chow, R; Gillies, A; Enns, R A; Telford, J J; Galorport, C
Abstract: Background: In Canada, British Columbia (BC) is the leading province in opioid deaths with 30.6 per 100, 000 population. Since substance users are stigmatized in health care, patient care requires specific, individualized management strategies, which often creates a gap between the patient and health care service. Diagnostic studies remain a challenge due to lack of funding and the unique requirements necessary to treat this patient population efficiently. Thus, new methods of prevention must be cultivated to ensure ideal patient care. Aims: To investigate the proportion of patients on restricted narcotics that failed to attend scheduled gastroenterology and hepatology appointments at our center. Methods: A retrospective chart review from 01/05 – 07/19 and data analysis of patients (≥ 19 yrs.) referred to a Downtown Gastroenterology office was performed. Data was collected from an electronic medical record system and filtered through a keyword search for 'Methadone', 'Suboxone', 'Dilaudid', and 'Morphine' to create a sample size of patients with recent/ongoing use of narcotic agents. Patients with chronic pain, or terminal illness prescribed these drugs were not included. Demographic information, type of appointment scheduled and failure to attend were recorded. Results: Acquired data yielded 2630 patients of which 350 patient were included. Mean age was 47 years (61% male). 35% of the patients were current narcotics users, the rest being previous users of these agents. Scheduled appointments and non-attendance are shown in Tables 2 and 3. Most patients (70%) were referred for various general GI complaints with HCV accounting for 23% of the consults. Despite the use of confirmation lines, 20% of HCV referred patients and 29% of non-HCV referred patients did not attend their first appointment. Conclusions: Current and prior narcotic users failed to attend more than one quarter of scheduled gastroenterology/hepatology appointments. Ideal management of care for GI disease can't be obtained without contact with those that provide the service. Creative, innovative management strategies are required to ensure ideal care for this unique group of patients. Funding Agencies: None